Longitudinal Observation of Outcomes and Patient Access to Integrated Care Following Point-of-Care Glycemic Screening in Community Health Center Dental Safety Net Clinics - Glurich, Ingrid; Berg, Richard; Panny, Aloksagar; Shimpi, Neel; Steinmetz, Annie; Nycz, Greg; Acharya, Amit (Frontiers in Oral Health, 2021)
Introduction: Rates of diabetes/prediabetes continue to increase, with disparity populations disproportionately affected. Previous field trials promoted point-of-care (POC) glycemic screening in dental settings as an additional primary care setting to identify potentially at-risk individuals requiring integrated care intervention. The present study observed outcomes of POC Hemoglobin A1C (HbA1C) screening at community health center (CHC) dental clinics (DC) and compliance with longitudinal integrated care management among at-risk patients attending dental appointments. Materials and Methods: POC HbA1c screening utilizing FDA-approved instrumentation in dental clinic settings and periodontal evaluation of at-risk dental patients with no prior diagnosis of diabetes/prediabetes and no glycemic testing in the preceding 6 months was undertaken. Screening of patients attending dental appointments from 10/24/2017 through 9/24/2018 was implemented at four Wisconsin- CHC-DC serving populations with high representation of disparity populations. Subjects meeting at-risk profiles underwent POC HbA1c screening. Individuals with measures in the diabetic/prediabetic range were advised to seek further medical evaluation and re-contacted after three months to document compliance. Longitudinal capture of glycemic measures in electronic health records for up to two years was undertaken for a subset (n=44) of subjects with available clinical medical and dental data. Longitudinal glycemic status and frequency of medical and dental access for follow-up care was monitored. Results: Risk assessment identified 224/915 (24.5%) patients who met inclusion criteria following two levels of risk screening, with 127/224 (57%) qualifying for POC HbA1C screening. Among those tested, 62/127 (49%) exhibited hyperglycemic measures, 55 in the prediabetic range and 7 in the diabetic range. Moderate-to-severe periodontitis was more prevalent in patients with prediabetes/diabetes compared to individuals with measures in the normal range. Participant follow-up compliance at 3 months was 90%. Longitudinal follow-up documented high rates of consistent access (100% and 80%, respectively), to the integrated medical-and-dental clinic environment over 24 months for individuals with hyperglycemic screening measures. Conclusion: POC glycemic screening revealed elevated HbA1C measures in nearly half of at-risk CHC-DC patients. Strong compliance with integrated medical/dental management over a 24-month interval was observed, documenting good patient receptivity to POC screening in the dental setting and compliance with integrated care follow up by at-risk patients.